Dengue Virus Infection Activates Interleukin-1β to Induce Tissue Injury and Vascular Leakage - Pan, Pan; Zhang, Qi; Liu, Weiyong; Wang, Wenbiao; Yu, Zhenyang; Lao, Zizhao; Zhang, Wei; Shen, Miaomiao; Wan, Pin; Xiao, Feng; Shereen, Muhammad Adnan; Zhang, Wen; et al. (Frontiers in Microbiology, 2019)
Dengue virus (DENV) infection causes diseases ranging from dengue fever to life-threatening dengue hemorrhagic fever and dengue shock syndrome characterized by endothelial dysfunction, vascular leakage, and shock. Here, we reveal a distinct mechanism by which DENV induces tissue injury and vascular leakage through promoting interleukin-1β (IL-1β) activation. DENV facilitates IL-1β secretion in infected patients, mice, human peripheral blood mononuclear cells (PBMCs), mice bone marrow-derived macrophages (BMDMs), and monocyte-differentiated macrophages (THP-1) via activating the NLRP3 inflammasome. Moreover, IL-1β induces vascular leakage and tissue injury in interferon alpha/beta receptor 1 deficient C57BL/6 mice (IFNAR-/- C57BL/6), whereas interleukin-1 receptor antagonist (IL-1RA) inhibits IL-1β-induced vascular leakage and tissue injury in mice. Finally, recombinant IL-1β protein can induce directly vascular leakage and tissue injury in C57BL/6 mice. Therefore, this study demonstrates a major contribution of IL-1β to DENV-associated pathology, and suggests IL-1RA acting as a potential agent for the infectious diseases.